Telemedicine in Malaysia and Indonesia: The importance, opportunities and challenges - OH, TICK HUI (WORLD SCIENTIFIC PUBL CO PTE LTD, 2006)
Telemedicine is an emerging industry with the potential to revolutionize the delivery of healthcare for the benefit of consumers, providers and payors. In general, telemedicine refers to the use of information and telecommunication technologies to distribute both information and expertise necessary for healthcare service provision, collaboration or delivery among geographically separated participants - physicians and patients. In short, it is a generic term which is used to define various aspects of healthcare at a distance. Telemedicine has been heralded as one of several possible solutions to some of the medical dilemmas that are faced by many developing countries. In this paper, we will discuss the current state of telemedicine in developing countries in South-East Asia (SEA) in general, with Malaysia and Indonesia in particular.